IMPLEMENTASI PENGAKUAN DAN JAMINAN HAM SEBAGAI UPAYA PENGUATAN INTEGRASI BANGSA - Nadir Nadir (Universitas Widya Gama Malang, 2019)
The existence of radicalism movement recently has made us worried about the nation and state life in the world order, since this movement is able to attract others from various elements of people and states that the teachings and ideology the movement offers are good. This movement at last will influence either the national or international stability because it is wellorganized. Therefore, it is necessary to reinforce the recognition and assurance of human rights especially the prosperity of the state that may make Indonesian people easy to be attracted by any offerings given by the groups of this radical movement. If in the past the movement of human rights was constructed by the thinkers due to arbitrarv rulers, at present human rights is moved and thought in order to strengthen the national integration. The alarming development of trans- national radicalism movements has given impacts on a national disintegration, therefore, the principle of recogmtion and assurance in the protection of human rights is lead to protect, save, and to assure the prosperity porn the state since few peoplejoining in a radical movement are not caused ofjihad but of economic reasons. If the state seriously give some recognition and assurance of human rights, the citizens feel to be protected. This in turns results in a sympathetic emphatic feelings to the government and the state, and therefore the national integration will still be kept intact and well-woven.